Exotic nuclear excitations - Pancholi, S.C.; SpringerLink (Online service). (New York Springer, 2011)
By providing the reader with a foundational background in high spin nuclear structure physics and exploring exciting current discoveries in the field, this book presents new phenomena in a clear and compelling way. The quest for achieving the highest spin states has resulted in some remarkable successes which this monograph will address in comprehensive detail. The text covers an array of pertinent subject matter, including the rotational alignment and bandcrossings, magnetic rotation, triaxial strong deformation and wobbling motion and chirality in nuclei. Dr. Pancholi offers his readers a clearly-written and up-to-date treatment of the topics covered. The prerequisites for a proper appreciation are courses in nuclear physics and nuclear models and measurement techniques of observables like gamma-ray energies, intensities, multi-fold coincidences, angular correlations or distributions, linear polarization, internal conversion coefficients, short lifetime (pico-second range) of excited states etc. and instrumentation and data analysis methods.
Rotational alignment and bandcrossings -- Magnetic rotation -- Triaxial strong deformation and Wobbling motion -- Chirality in nuclei.
Keywords: Physics; Nuclear physics; Nuclear Physics, Heavy Ions, Hadrons; Nuclear Fusion; Electronic books